Actualization of Pancasila Values in the Topat War Tradition Based on Local Wisdom - Arini Hubbi Farodisa; Hafsah Hafsah; Saddam Saddam; Malami Muhammad Garba; Aliahardi Winata (Yayasan Keluarga Guru Mandiri, 2024)
The research aims to explore how these values are embodied through tradition and how they influence the community. Using a qualitative approach with a phenomenological method, the study collects data through observation, interviews, and documentation. The findings indicate that the Topat War tradition effectively embodies the values of Pancasila divinity, humanity, unity, democracy, and justice in its preparation and execution. These values are evident during the celebration and permeate the daily lives of the local community. The study concludes that the continuity of the Topat War tradition is maintained as the community upholds Pancasila values without altering the essence of their local wisdom, despite modernization. The tradition is now recognized internationally as part of the Nusantara Event Charm. This research contributes to understanding how local traditions can be a medium for actualizing national values, offering insights into integrating cultural practices with national ideology and preserving cultural heritage.